Acute vascular rejection after kidney transplantation outcome and effect of different therapeutic modalities - Wafa, Ehab Wahba; Fouda, Mohamed Ashraf; El Baz, Mahmoud; Moustafa, Amany; Ghoneim, Mohamed A (African Journal of Nephrology, 2016)
Background: Steroid resistant acute vascular rejection (AVR) is a great obstacle in successful renal transplantation (KTx). The aim of this work was to evaluate the outcome of histologically confirmed acute vascular rejection - which occurred in severe aggressive form in 39 patients following kidney transplantation as well as to study the outcome of therapy. These cases were chosen from 1000 renal allograft recipients who underwent kidney transplantation in the period between March, 1976 and April 1997 in Urology-Nephrology Center, Mansoura, Egypt. Methods: Statistical analysis of risk factors leading to AVR was carried out. The outcome of different rescue therapies used for AVR as well as graft survival functions were also analyzed. Results: Survival analysis for grafts with AVR revealed 60%, 53%, 30 %, 0% graft survival at 1, 2, 5, 10 yrs respectively after Tx. A statistically significant difference was found in comparison to patients who only experienced acute cellular rejection (90%, 84%, 71%, 46% graft survival at 1, 2, 5, 10 years post- KTx respectively) or patients who passed without rejection in their post-transplantation follow up (95%, 91.3%, 83.3%, 65.5% graft survival at 1, 2, 5, 10 yrs respectively). No statistically significant difference on the overall graft survival between the different modalities of therapy was noted. Steroid pulses + plasma exchange were given for 14 patients with AVR, whereas ATG, MAB ± plasma exchange were added to steroid resistant cases (25 patients). Logistic regression analysis of these data showed that prior blood transfusion, donor-recipient consanguinity, retransplantation are the most significant variables related to occurrence of AVR after kidney transplantation. At last follow up, 14 patients 35.9%) were living with functioning grafts, 16 patients (41%) were living on dialysis, 5 patients died with functioning grafts (12.8%) and 4 patients (10.25%) died with failed grafts. In conclusion: AVR remains a major obstacle for renal transplantation as it markedly impaired graft survival and responded poorly to therapy. Prior blood transfusion decreased the incidence of AVR whereas retransplantation and unrelated donation account significantly to the occurrence of AVR after renal Tx.